Tensile Strength of Warm Rubberised Asphalt Mixtures Produced Using Dry Method - Rosnawati Buhari, (International Journal of Integrated Engineering, 2025)
Recycling crumb rubber in the asphalt industry is an excellent way to reduce the wastage of this byproduct. It has been demonstrated that crumb rubber obtained from used tyres can be used as an addition or replacement material to enhance the characteristics of asphalt mixtures. Considering the importance of expanding a technology for a greener future, producing a crumb rubber warm asphalt mixture (CRWMA) is the aim of this study. This study focuses on investigating the resilient modulus and moisture susceptibility of the asphalt mixtures. The AC14 samples were prepared by replacing 2% to 4% of the net weight of aggregate with crumb rubber, and 3% Sasobit from the total weight of the optimum binder content was used to modify the base binder. The JKR specification and Marshall mix design were used to obtain the optimum binder content of the samples. The effect of crumb rubber proportion in asphalt mixture was determined by observing the mixture's volumetric properties, resilient modulus and moisture susceptibility. The results show that asphalt mixture incorporated with crumb rubber had a greater resilient modulus and indirect tensile strength, even though it was produced at 20°C lower than hot mix asphalt, compared to a conventional asphalt mixture. It indicates that crumb rubber has improved the elasticity of the samples. In conclusion, a combination of 3% crumb rubber and 3.0% Sasobit is the optimum composition for producing a better performance of warm rubberised asphalt mixture compared to a conventional asphalt mixture.